The Impact of Instagram on Enhancing Descriptive Writing Skills in Eighth Grade Students at SMP Negeri 1 Padangsidimpuan - Nisa, Khoirun; Sibuea, Erni Rawati; Mahrani (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
This study investigates the effectiveness of using Instagram as a tool to enhance students' descriptive writing skills at SMP Negeri 1 Padangsidimpuan. Utilizing the Class Action Research (CAR) method, the research involved pre-tests, post-tests, and two cycles of intervention with 30 eighth-grade students. Initial findings indicated that students' writing skills were categorized as poor, with an average pre-test score of 59.83. Following the integration of Instagram in the instructional process, students' average scores improved significantly to 66.5 in Cycle 1 and 82.5 in Cycle 2. The overall improvement from pre-test to post-test 2 was 37.89%, with 83.33% of students meeting the Minimum Mastery Criterion (KKM). These results confirm the hypothesis that Instagram can significantly improve students' descriptive writing skills. The study suggests that incorporating social media in educational practices can enhance student engagement and learning outcomes. It also highlights the potential for further research on the use of digital tools in education to foster innovative teaching methods.